First-Principles Calculations to Investigate Structural, Spectroscopic Features, Electronic and Thermodynamic Properties of Trichloroacetaldehyde - Basnet, Bishwo; Rana Magar, Abhishek; Ghimire, Rabin; Joshi, Usha; Rai, Krishna Bahadur (Himalayan Journal of Science and Technology, 2024)
Trichloroacetaldehyde is an oily liquid which has pungent smell with irritating odor. DFT with B3LYP/6-311++G (d, p) basis set together with Gauss Sum 3.0.2 and Moltran software were used to study this molecule. The molecule's optimization energy was found to be -41707.52 eV. From the FT-IR spectroscopy, the C-H stretching vibration are observed at 2974 cm-1. The C=O stretching, C H stretching, C–Cl stretching, C–H bending vibrations are also seen at various spectrum modes. The molecular electrostatic potential and electrostatic potential have shown that the region near oxygen has highest electrophilic activity and the region near hydrogen has the highest nucleophilic activity. The electrostatic potential on to the surface with electron density allows visualization of the molecule's size, shape, charge density and reactive sites. HOMO-LUMO energy gap has a significant stability index and its value is 5.99 eV. Density of states (DOS) allows us to stimulate electrons moving from the valence band into the conduction band and its value is 6.01 eV and is very much close to energy gap (5.99 eV) obtained from HOMO-LUMO gap. The global reactivity parameter i.e. hardness is 2.99 eV, softness is 0.33 eV⁻¹, chemical potential is -5.47 eV, electronegativity is 5.47 eV and electrophilicity index is 5.00 eV, has been observed. Mulliken atomic charges analysis shows that atoms Cl2, Cl3, Cl4 and C5 along with O7 have negative charges and C1 and H6 atoms contain positive charge. The thermodynamic parameters i.e. heat capacity at constant volume, heat capacity at constant pressure, internal energy, enthalpy and entropy increase except Gibb’s free energy with rise in temperature.